The Influences of Competence and Motivation on Performance by Way of Reward as Moderating Variable (A Case Study in Regional Financial Management of Bulungan Regency Administration) - Hamzah, Mochamad; Rosidi, Rosidi; Mardiati, Endang (Journal of Accounting and Business Education, 2017)
This study aimed at analyzing and examining the influences of competence and motivation on the regional finance management performance using regional performance incentive/reward asÂ  moderating variable. The employed analysis mode is PLS (Partial Least Square). The study was carried out at the regional work units in Bulungan. The sampling technique was purposive sampling. The results of this study indicates that competence and motivation variable positively influence the performance of regional financial managers. Performance financial incentive has yet to be proven to strengthen competence effect on the performance of regional financial managers, but it has proven to strengthen the influence of motivation on the performance of the regional financial managers. Thus, it can be concluded that the higher the competence and motivation of regional financial managers, the performance will increase. The employeesâ motivation are increasing when policymakers reward them the incentive as an appreciation to achieve better performance.Â Keywords Â Â : competence, motivation, performance, regional performance incentive